Tracing New Urbanism's Suburban Intervention in Minneapolis–St. Paul. (March 2018) - Trudeau, Dan
New Urbanism (NU) is an urban planning movement that aims to curtail suburban sprawl. Critics argue that NU actually contributes to sprawl. However, such claims overlook the diverse ways in which NU is implemented. This article contributes to the study of suburban development by examining two different types of NU projects in suburban Minneapolis–St. Paul and comparing these with a control case. Using surveys of the projects' built environments and residents' travel behavior and attitudes toward neighbors, the article finds that the NU projects break away from the physical and functional dimensions of sprawl, yet reproduce the social dimensions.